Large-scale assembly of single-walled carbon nanotubes based on aqueous solution. Issue 190 (13th June 2018) - Zhang, Jianwei; Cui, Jianlei; Wang, Xuewen; Wang, Wenjun; Mei, Xuesong; Long, Weimin; Sun, Huawei; He, Xiaoqiao; Xie, Hui
ABSTRACT: Carbon nanotubes (CNTs) have been published for nearly thirty years and proved to have potential in the development of high-speed and power-efficient logic applications, but commercial applications are rarely reported. The main reason is the precise placement of CNTs on a substrate. Among the methods for assembly in solution, self-assembly is a promising way to organize CNTs in topologies. Compared with external force/field assembly, it does not need any external force or field, while the pattern is clearer than that fabricated by film aided assembly. In this work, we demonstrate a simple large-scale assembly of single-walled carbon nanotubes based on aqueous solution, using an evaporation-driven dip-casting process onto a topographically heterogeneous interface of alternating hydrophobic n-Octadecyltrimethoxysilane (OTS) strips on the hydrophilic SiO2 substrate fabricated by μCP. The results show that μCP is a very convenient and economical technique for forming patterned self-assembled monolayer (SAM) with features having dimensions of the mould. With the evaporation-driven dip-casting process, the density of SWNTs can be improved at lower concentration and the selective deposition of SWNTs happens which can be arranged in a single or fewer layers.